Association between visual performance and aberration using quality of life impact of refractive correction (QIRC) questionnaire in moderate and high myopic patient - Md Rejab, Noor Shazana; Hilmi, Mohd Radzi; Mohd. Kamal, Khairidzan; Wolffsohn, James S (IIUM Press, 2023)
Introduction: This study aimed to evaluate the association between visual performance and aberration using quality of life impact of refractive correction (QIRC) questionnaire in moderate and high myopic groups. Methods: 120 eyes of 60 participants were recruited and both right and left eyes of the myopic subjects were measured separately. For satisfaction in visual performance, Quality of Life Impact of Refractive Correction (QIRC) questionnaire were given to all participants. For aberration measurement, WASCA wavefront analyser were done in dimmed illuminated room. Aberration was recorded as root mean square (RMS). WASCA built-in wavefront analysis computed three best measurements of RMS for third and fourth orders of aberration. The average of three measurements were taken for analysis. All data were expressed in mean and standard deviation. Statistical analyses were performed using Predictive analytics software. P < 0.05 was set as the level of significance. Independent T-test were done to compare all parameters between moderate and high myopia, including QIRC scores. Results: This study found the mean QIRC scores were approximately similar between moderate and high myopia (Both P > 0.05). However, high order aberration (HOA) comprise of third and fourth order aberration were found significantly higher in high myopia group compared to moderate myopia group (Both P < 0.05). Conclusion: This study found that QIRC questionnaire could not be able to differentiate subjective visual performance between moderate and high myopia.